Eat, Pray, Love: The Representation of Italy, India, and Indonesia as Exotic Destinations - Meita Annisa Nurhutami (Passage, 2013)
The research is a descriptive study of the representation of the cultures of Italy, India, and Indonesia in the novel Eat, Pray, Love (2006). The purpose of the research is not only to depict the way the traveler represents the three countries, but also to reveal the traveler’s manner towards the differences of the host cultures – Italy, India, and Indonesia – compared to her cultural origin. As a novel which contains travelling experiences and descriptions about the host culture, Eat, Pray, Love shows the tendency of the writer’s supreme attitude towards the cultures of the three countries. To answer the formulated research problems, the study uses Victor Segalen’s (2001) notions of Exoticism which emphasizes exoticism as the notion of difference: the perception of diversity. The research employed qualitative approach and was presented in a descriptive method. The findings of the study show that the three countries are exotic destinations in terms of their cultural, religious, and economic levels. The cultures of the three countries are exotic characterized by three aspects: the existence of the observer’s desires towards the observed object, the ability of the observed object in fulfilling the observer’s desire for exotic experience, and the remoteness of the observed object. From the analysis, it is found that the traveler gradually respects and appreciates the heterogeneity of the host culture’s world views.Keywords: Representation, Travel Writing, Exotic, Exoticism, Supremacy